Permainan Edukatif dan Kreatif Ular Tangga Menurunkan Dampak Negatif Gadget pada Anak - Erna Julianti; Elni Elni (Sekolah Tinggi Ilmu Kesehatan Baiturrahim Jambi, 2021)
The gadgetis one of the current technology development used by all groups of people, including children. School-age children (7-11 years old) use a gadget since their parents are busy to work and the price of the gadget is getting cheaper due to market competition. The frequently occurred problem these days is that children often use their gadgets to play games more than studying or playing outside their house with their same-age friends. When the children at home, it gets difficult to communicate with them, they are being indifferent and do not respond to what their parents say. Besides, the gadget also causes a problem in children’s motor development and eye health. This community service was conducted at a public elementary school, namely SD Negeri 21 Pangkal pinang. It was conducted in December 2019. The target was elementary level students. The method of this community service was done through an educative and creative, namely snake and ladder. The result showed a significant average value between the knowledge before (pre-test) and after the treatment (post-test) by using the educative and creative, namely snake and ladder. There was an increase in the average value of children’s knowledge after playing snake and ladder game by 18.69. It is expected that there is supervision from the family when the students use a gadget. Family is also expected to explain the information obtained by the children from the Internet and also give the children a duration when playing games using a gadget to prevent them from its negative impacts, such as vision problems.